Visibility of microvessels in Optical Coherence Tomography angiography depends on angular orientation. Issue 10 (28th July 2020) - Zhu, Jun; Bernucci, Marcel T.; Merkle, Conrad W.; Srinivasan, Vivek J.
Abstract: Optical Coherence Tomography angiography (OCTA) is a widespread tool for depth‐resolved imaging of chorioretinal vasculature with single microvessel resolution. To improve the clinical interpretation of OCTA, the conditions affecting visualization of microvessels must be defined. Here we inject a scattering plasma tracer (Intralipid) during OCTA imaging of the anesthetized rat eye. In the retina, we find that interlaminar (vertical) vessels that connect laminae have one‐fourth to one‐third the OCTA red blood cell to tracer (RBC‐to‐tracer) signal ratio of intralaminar (horizontal) vessels. This finding suggests that the OCTA signal from microvessels depends on angular orientation, making vertically‐oriented vessels more difficult to visualize using intrinsic contrast alone. Clinicians should be aware of this potential artifact when interpreting OCTA. Abstract : Optical Coherence Tomography angiography (OCTA) visualizes microvessels without an exogenous contrast agent and enjoys widespread clinical use. Angiography is based on intrinsic backscattering from moving red blood cells, but it is not known how well angiography can detect and visualize red blood cells in microvessels of differing orientations. Here, using an intravascular tracer as a reference, we show that intrinsic angiography often misses vertical retinal vessels, parallel to the incident light.